Cerebrospinal fluid neurohypophysial peptides in benign intracranial hypertension. Issue 12 (December 1988) - Seckl, J; Lightman, S
Abstract : The cerebrospinal fluid (CSF) concentrations of arginine vasopressin (AVP) and oxytocin (OT) were investigated both in patients with benign intracranial hypertension and in age and sex matched controls. Twenty eight lumbar punctures were performed on 15 patients with benign intracranial hypertension as part of their routine investigation and therapy. All patients had raised intracranial pressure (27.4, SE 1.7 cm.CSF). CSF AVP levels were significantly elevated in benign intracranial hypertension (2.1, SE 0.3 pmol/l) compared with controls (0.7, SE 0.1 pmol/l, p less than 0.001) but CSF OT concentrations were similar in both groups. CSF osmolality and plasma AVP and osmolality were identical in patients and controls. There was no correlation between CSF AVP concentration and intracranial pressure. The selective elevation of AVP in CSF may be of importance in the pathogenesis of raised intracranial pressure in benign intracranial hypertension.